Management style of division and section heads of the city accounting department Quezon City : a study - Arceo, Nora C. (Manila : National University, 2009)
This study is expected to give every researcher a clear view of the management style of department heads and section chiefs in the accounting department of the city government.
Chapter 1. The Problem and its setting -- Chapter 2. Review of related literature and studies -- Chapter 3. Methodology -- Chapter 4. Presentation, Analysis, and Interpretation of Data -- Chapter 5. Summary, Conclusion, and Recommendation.
Research Method : Descriptive Method.
Includes bibliographical references.